Company Profile Café Teras Muzaka - Miranda Syafrina; Eko Purnomo (Jurnal Riset Rumpun Seni, Desain dan Media, 2023)
Café Teras Muzaka established since 2020 is a contemporary café that stands in the center of Lubuk Basung sub-district, this café carries an elegant and minimalist concept. Café Teras Muzaka is always the first choice, a lot of people from various circles come to celebrate moments, meetings or just spend their free time. The findings of the problems of Café Teras Muzaka, namely in terms of publicity, have not used effective promotional media, resulting in a lack of Brand Awareness of consumers and potential consumers of Café Teras Muzaka. Therefore, this design aims to design a Company Profile video that can be a source of information for the public about Café Teras Muzaka. The design uses the 4D method (Define, Design, Develop, and Disseminate). Therefore, by using video company profile as the main media, it is possible to produce a company profile that can not only increase Brand Awareness, but also become an effective publicity media.